How does soil carbon sequestration affect greenhouse gas emissions from a sheep farming system? Results of an life cycle assessment case study - Pasquale Arca; Enrico Vagnoni; Pierpaolo Duce; Antonello Franca (Italian Journal of Agronomy)
Highlights